Krisis Konsumerisme Kapitalistik: Solusi Islam melalui Gaya Hidup Halal Minimalis dan Koperasi Syariah - Sufiansyah, Jerry; Sri Wahyuni, Rizka (Journal of Islamic Economics Studies and Practices, 2025)
This article discusses the crisis of capitalist consumerism characterized by the global rise of consumer culture influenced by advertising and instant lifestyles. This phenomenon leads to a moral crisis in the market, where values of simplicity and life balance are neglected. Islam offers solutions through the concepts of halal minimalist lifestyle and sharia cooperatives. The halal minimalist lifestyle, rooted in the teachings of zuhd, emphasizes simplicity, avoiding wastefulness, and focusing on essential needs. This concept aligns with the principle of moderation in consumption taught in Islam. Additionally, sharia cooperatives, as community-based economic institutions, support equitable wealth distribution and reduce social disparities. This article aims to examine how the implementation of halal minimalist lifestyle and sharia cooperatives can serve as alternatives in addressing the crisis of capitalist consumerism and how both can contribute to the formation of a more just and sustainable society.